Escarlatina en la ciudad de Mercedes - Sanguinet, Pedro; Castellanos, Federico; Vidal y Fuentes, Alfredo; Prado, P. (Boletín Consejo Nacional de Higiene, 1914)
Informe de la Inspección Departamental de Higiene de Soriano